PENGARUH TINGKAT HUNIAN HOTEL DAN JUMLAH WISATAWAN TERHADAP PENDAPATAN SEKTOR PARIWISATA DI KABUPATEN KEPULAUAN SANGIHE - Freety Michela Pangimangen; Ita Pingkan F. Rorong; Steeva Y.L Tumangkeng (PT. Hasba Edukasi Mandiri, 2025)
The role of the national tourism sector is increasingly important in line with the development and contribution made by the tourism sector through foreign exchange revenue, regional income, regional development, and in the absorption of investment and manpower as well as business development spread across various parts of Indonesia. The goal that this research wants to achieve is to know How does the hotel occupancy rate and the number of tourists affect the tourism sector's income in Sangihe Islands Regency. The method of analysis used in this study is Multiple Regression Analysis. As a result of the study, it is known that the hotel occupancy rate variable has a significant influence on tourism sector income in Sangihe Islands Regency, the number of tourists has a significant influence on tourism sector income in Sangihe Islands Regency. Together, the variables The hotel occupancy rate and the number of tourists have a significant influence on the income of the tourism sector in the Sangihe IslandsRegency